Three consecutive nights of sleep loss: Effects of morning caffeine consumption on subjective sleepiness/alertness, reaction time and simulated driving performance. (April 2020) - Bartrim, Karly; McCarthy, Brianna; McCartney, Danielle; Grant, Gary; Desbrow, Ben; Irwin, Christopher
Highlights: Sleep loss increased tiredness and decreased alertness and concentration. Sleep loss did not influence driving performance or choice reaction time. Caffeine only marginally alleviated the subjective effects of sleep loss. Abstract: Caffeinated products are often consumed as a popular countermeasure to the effects of sleep loss. However, the efficacy of caffeine to exert these effects after consecutive nights of sleep loss is poorly understood. The aim of this study was to investigate the effects of three consecutive nights of restricted sleep and morning caffeine consumption on subjective ratings of sleepiness/alertness, reaction time, and simulated driving performance. Twenty healthy, habitual caffeine consumers (11 females; age: 23.3 ± 5.7 y; BMI: 22.3 ± 3.5 kg⋅m −2 ; caffeine intake: 204 ± 89 mg⋅day −1 ; Mean ± SD) who had normal sleeping patterns (≥8 h⋅night −1 ) participated in this double-blind, placebo-controlled, randomised study. Following one night of normal sleep (≥8 h time in bed (TIB)), participants underwent three consecutive nights of restricted sleep (5 h TIB). Participants received caffeine (200 mg; n  = 10) or placebo ( n  = 10) capsules each morning and all participants received caffeine (100 mg) capsules each afternoon. Subjective ratings of alertness, concentration and tiredness were measured before and 1 h after morning capsule administration. Choice Reaction Time (CRT) was examined 1 h after morning capsule administration, with response speed and accuracy as outcome variables. Driving performance was assessed using a 30 min simulated driving task, with lateral (standard deviation of lane position [SDLP]; total number of line crossings [LC]) and longitudinal (standard deviation of speed [SDSP]) measures of vehicle control as outcome variables. Alertness and concentration significantly decreased, and tiredness increased across the three days of sleep loss. Caffeine only marginally alleviated these effects. No differences were observed between treatments or across trial days for response speed and accuracy on the CRT task. Likewise, no significant differences were observed between groups or across trial days for any measures of simulated driving performance. Overall, results from this study indicate that three consecutive days of sleep loss influence subjective ratings of alertness, concentration and tiredness, but does not alter CRT or simulated driving performance. Caffeine may alleviate some of the negative subjective effects imposed by restricted sleep, but the efficacy of caffeine to attenuate performance changes in CRT and driving performance were unable to be observed.